Price Discount, Paylater, Shopping Lifestyle and Impulse Buying Shopee Users - Budi Suryowati; Dini Mutia Alifah (Jurnal Simki Economic, 2025)
This study aims to analyze the influence of a price reduction, paylater, shopping habits and impulsive purchases in Shopee users in Jakarta. The quantitative approach was used by a survey method through an online questionnaire involving 100 respondents chose utilizing purposive methods for sampling. The information was SEM-PLS, or structural equation modeling-partial least squares, was used for the analysis to see how the influence of a price reduction, paylater, and lifestyle of shopping variables on impulsive purchases. The study's findings show that price discounts in the form of consumer perception of the amount of discounts, the period of discounts, and the frequency of use of discounts affect impulse buying. Paylater is in the form of ease of access to services, and benefits. It also affects impulse buying. In addition, shopping frequency, interest in shopping trends, and the tendency to shop without planning which are indicators of shopping lifestyle also have an impact on impulse buying. These findings indicate that Shopee's marketing strategy that combines discounts, credit systems, and lifestyle-based promotions plays a big role in encouraging consumptive behavior. Therefore, financial education for consumers and more responsible e-commerce policies are needed to control the risk of impulse shopping.